Nitrogen-sensitized dual phase titanate/titania for visible-light driven phenol degradation - Schreyer, Martin K. (2013)
A dual-phase material (DP-160) comprising hydrated titanate (H2Ti3O7·xH2O) and anatase (TiO2) was synthesized in a low-temperature one-pot process in the presence of triethylamine (TEA) as the N-source. The unique structure exhibits strong visible light absorption. The chromophore is linked to Ti–N bonds derived from both surface sensitization and sub-surface (bulk) doping. From transmission electron microscope (TEM) and textural studies by N2 physisorption, the composite exists as mesoporous particles with a grain size of ∼20 nm and mean pore diameter of 3.5 nm, responsible for the high surface area (∼180 m2/g). DP-160 demonstrated photocatalytic activity in the degradation of phenol under visible light (λ>420 nm). The activity of the composite was further enhanced by a small addition (0.001 M) of H2O2, which also gave rise to some visible light activity in the control samples. This effect is believed to be associated with the surface peroxo-titanate complex. GC–MS analyses showed that the intermediate products of phenol degradation induced by visible light irradiation of DP-160 did not differ from those obtained by UV (band-gap) irradiation of TiO2. The overall performance of the composite is attributed to efficient excitation via inter-band states (due to N-doping), surface sensitization, improved adsorptive properties of aromatic compounds due to the N-carbonaceous overlayer, and the presence of heterojunctions that are known to promote directional charge transfer in other mixed-phase titanias like Degussa P25.